Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Bandung Barat - Raudhatul, Azmi; Farouq Ishak, Jouzar (Indonesian Accounting Research Journal, 2023)
This paper aims to examine three competencies (i.e., HR competence, SPIP implementation, and SIPD implementation) in Bandung Barat Regency towards the quality of Local Government financial reports. Data were collected from 90 respondents from human resources in Bandung Barat Regency, Indonesia. Multiple linear regression analysis was employed to evaluate HR proficiency, SPIP implementation, SIPD implementation, and the quality of Local Government financial reports. The significance of this study lies in its potential to influence the auditor's evaluation of the financial statements of regional governments by enhancing the competence of the apparatus, internal control systems, and development factors of local government information systems for the local government of Bandung Barat Regency. The sole signal in the Bandung Barat Regency was the focus of this investigation, which has the drawback that the results of a comparable study on another study object can provide different results. Nonetheless, several areas were identified that the local government can explore to enhance credibility and the auditor's perspective. Keywords: HR Competence, SPIP Implementation, SPID Implementation, Quality of Local Government Financial Reports